Pengaruh Subsidi Pemerintah Terhadap Keberlanjutan Usaha Pedagang Kecil: Studi Pada Pasar Tradisional - Dony Hidayat; Lalu Adiyatma Taopikul Hadi; Junaidin (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2024)
Small traders often face various challenges in developing their businesses, such as competition from modern retailers, limited capital, low access to technology, and lack of understanding in financial management and business management. This study aims to analyze the effect of government subsidies on the business sustainability of small traders in traditional markets. This study uses a quantitative approach with a sample of 100 people in Sweta Traditional Market, Mataram, West Nusa Tenggara from February to July 2024 who have received subsidies from the government. Descriptive analysis was used to describe the characteristics of respondents and simple linear regression analysis was used to test the effect of government subsidies on the sustainability of small traders' businesses. The results showed that government subsidies have a positive influence on the sustainability of small-scale traders' businesses (p-value 0.02). Thus, government subsidies have a positive effect on the sustainability of small traders' businesses in traditional markets, especially in improving profitability and competitiveness